Leadership and ICTs implementation for rural development - Md Ram, Aizuddin; Aziz, Faiq; Razali, Fazilah; Yusof, Mat Rahimi (Science and Engineering Research Support Society, 2020)
This study aims to explore the implementation of ICTs in rural development and the role played by community leaders. The study was conducted on 10 selected rural communities in the state of Terengganu. This study adopts the qualitative method, specifically, the phenomenology approach. This study focuses on target groups to achieve the research objectives. The data were collected from interviews using Focus Group Discussion (FGD) and official printed document. The results of this study provide a clear picture of the potential of ICT use in terms of economic development, education and social development of rural communities. This study also examines the support of local leaders as the agents of change, especially in the field of Information communication technology (ICT) to accelerate the development process in rural areas. In conclusion, ICT can be potentially used by people in the rural area with the participation and collaboration of the members of the community, community leaders, government agencies, the private sector and ICT industry players.